2021
DOI: 10.1111/ppc.12872
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between internet addiction and risky health behaviors in university students: A cross‐sectional study in Turkey

Abstract: Purpose:The study was carried out to determine the relationship between internet addiction and risky health behaviors in university students.Design and Methods: The study, which is cross-sectional research, was conducted with 606 university students in the 2019-2020 academic year and used face-to-face interviews.Findings: It was determined that 7.15% of the students had internet addiction with limited symptoms. A positive and significant relationship was found between internet addiction and risky health behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The total scores were the sum of the coded responses. Based on this, depressive symptoms were identified as follows: no depressive symptoms (0-4), mild depressive symptoms (5)(6)(7)(8)(9), moderate depressive symptoms (10)(11)(12)(13)(14), moderately severe depressive symptoms (15)(16)(17)(18)(19), and severe depressive symptoms (20 or more). Anxiety symptoms were identified as follows: no anxiety symptoms (0-4), mild anxiety symptoms (5)(6)(7)(8)(9), moderate anxiety symptoms (10)(11)(12)(13)(14), and severe anxiety symptoms (15 or more).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total scores were the sum of the coded responses. Based on this, depressive symptoms were identified as follows: no depressive symptoms (0-4), mild depressive symptoms (5)(6)(7)(8)(9), moderate depressive symptoms (10)(11)(12)(13)(14), moderately severe depressive symptoms (15)(16)(17)(18)(19), and severe depressive symptoms (20 or more). Anxiety symptoms were identified as follows: no anxiety symptoms (0-4), mild anxiety symptoms (5)(6)(7)(8)(9), moderate anxiety symptoms (10)(11)(12)(13)(14), and severe anxiety symptoms (15 or more).…”
Section: Methodsmentioning
confidence: 99%
“…Relationships, acceptance and integration, academic performance, meeting expectations, but also future employability are important aspects at this time. The consequences of problematic internet use by college students can be poor academic performance, disinterest in engaging in other activities, excessive daytime sleepiness ( 7 ), poor sleep quality ( 8 ), reduced academic engagement (dedication and vigor) ( 9 ), risky health behaviors ( 10 ), but also health problems, such as being under- or over-weight ( 11 , 12 ), migraine ( 12 , 13 ), back pain ( 12 ), or increased resting heart rate ( 14 ). These are reasons for increased vigilance about young people's use of the internet.…”
Section: Introductionmentioning
confidence: 99%
“…22 Özarıcı and Cangöl Söğüt found a significant difference between students' Internet Addiction Scale scores and their age, perception of friendship relations, perception of school success and leisure activities. 30 According to our results, it is possible to say that those who think that their relationships are not affected spend less time on the internet, internet use does not prevent their social lives and they more rarely feel alone.…”
Section: Discussionmentioning
confidence: 64%
“…SI, SP, and SA are all predictive factors for future suicide deaths [25], while NSSI behavior has a certain predictive role in increasing suicide risk [26]. A large amount of research has demonstrated a positive correlation between adolescent IA and suicidal and selfharm behaviors [27][28][29]. However, Liu et al [30]demonstrated that after controlling for depression variables, there was no correlation between adolescent IA and NSSI.…”
Section: Introductionmentioning
confidence: 99%